Accountability and Transparency in Vote Recount ss Good Governance Practice in Sidenreng Rappang - Niwadi, Ramli; Nonci, Nurjannah; Razak, Muhammad Rais Rahmat; Lubis, Sandi; Sundari, Sundari (Universitas Muhammadiyah Sorong, 2025)
Applying accountability and transparency in the vote recount (PSU) process is crucial in ensuring good governance and electoral integrity. This study aims to analyze the implementation of these principles in Sidenreng Rappang District, particularly during the recount process in response to electoral violations. Using a qualitative approach with descriptive-analytical methods, the research involved in-depth interviews with key informants, document analysis, and participatory observation. The results show that while transparency efforts were made through information dissemination via official channels, many citizens still relied on informal sources for updates. Furthermore, the accountability process faced challenges, such as a lack of standardized reporting and weak communication between election authorities and the public. The study concludes that despite normative principles of good governance, the actual practice of PSU in Sidenreng Rappang District falls short regarding transparency and accountability. It is essential to improve the technical capacity of election organizers, enhance public participation, and strengthen oversight mechanisms to ensure legitimacy and public trust in the electoral process.